2022
DOI: 10.1155/2022/9684062
|View full text |Cite
|
Sign up to set email alerts
|

Irisin Ameliorates Intervertebral Disc Degeneration by Activating LATS/YAP/CTGF Signaling

Abstract: Unbalanced metabolism of an extracellular matrix (ECM) in nucleus pulposus cells (NPCs) is widely acknowledged as the primary cause of intervertebral disc degeneration (IDD). Irisin, a novel myokine, is cleaved from fibronectin type III domain-containing 5 (FNDC5) and has recently been proven to regulate the metabolism of ECM. However, little is known about its potential on NPCs and the development of IDD. Therefore, this study sought to examine the protective effects and molecular mechanism of irisin on IDD i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
(53 reference statements)
1
2
0
Order By: Relevance
“…Interestingly, as the duration of caudal compression in rats increased or as the degree of human disc degeneration increased, YAP expression signi cantly decreased, while TAZ expression further increased, suggesting that these two components may play different roles. Most of the literature has reported that the expression of YAP can delay the progression of disc degeneration [29,[55][56][57][58], and the present study showed that YAP expression levels were signi cantly increased in mildly degenerated nucleus pulposus tissue but were decreased in severely degenerated nucleus pulposus tissue. Acute disc injury can cause the upregulation of YAP expression, suggesting that IVDD has a certain ability to repair itself [29].…”
Section: Discussionsupporting
confidence: 61%
“…Interestingly, as the duration of caudal compression in rats increased or as the degree of human disc degeneration increased, YAP expression signi cantly decreased, while TAZ expression further increased, suggesting that these two components may play different roles. Most of the literature has reported that the expression of YAP can delay the progression of disc degeneration [29,[55][56][57][58], and the present study showed that YAP expression levels were signi cantly increased in mildly degenerated nucleus pulposus tissue but were decreased in severely degenerated nucleus pulposus tissue. Acute disc injury can cause the upregulation of YAP expression, suggesting that IVDD has a certain ability to repair itself [29].…”
Section: Discussionsupporting
confidence: 61%
“…A recent study suggested a correlation between LCN-2 and the expression of inflammation-related genes in human discs ( 114 ). Moreover, upregulated expression of LCN-2 has been validated to increase MMP-9 activity in AF cells ( 115 ). Considering that LCN-2 could function as a biomechanical and inflammatory sensor in bone–cartilage crosstalk, its specific role in IVDD needs to be elucidated ( 9 ).…”
Section: Osteokinesmentioning
confidence: 99%
“…Exercise elevated irisin levels in plasma and NP tissue and FNDC5/irisin knockout abolished the protective effects of exercise against IVDD in a murine model ( 114 ). By activating autophagy or large tumor suppressor kinase (LATS)/yes-associated protein (YAP)/connective tissue growth factor (CTGF, also known as CCN2) signaling, irisin can help maintain cellular activity and matrix metabolism balance and inhibit inflammatory effects, thereby decelerating the progression of IVDD ( 115 , 117 ).…”
Section: Myokines and Cardiokinesmentioning
confidence: 99%